(untitled) (Research, Society and Development, 2020)
This study aims to verify the level of physical activity and health risk behaviors of students of the Physical Education course of a public university in the interior of Rio Grande do Sul, Brazil, from a descriptive exploratory study of a quantitative character. The International IPAQ questionnaire was used to assess the level of physical activity and the Global School-based Student Health Survey questionnaire for health risk behaviors. It was found that 75% of students perform physical activities beneficial to health with intensity and duration. Among the variables, there was a significant association between the consumption of drink alcohol and tobacco consumption (p = 0.009), between self-perceived health and consumption of drink alcohol (p = 0.019) and smoking consumption (p = 0.025), one positive linear trend between the use of illicit drugs and the semester attended (p = 0.048) and, a negative linear trend between the semester attended and the consumption of fruits/vegetables (p = 0.043). It was concluded that most of those surveyed perform physical activities habitually, but maintain an inadequate diet, drink alcohol, use tobacco and, a small percentage, use illicit drugs frequently. Despite having health risk behavior, they are aware of the harmful effects of these behaviors.